Mos2nts as a novel drug delivery system for oxaliplatin anticancer drug in the presence p and ga impurities in different sites - Hamid Neamah, Mohammed; H. Mohammed, Mohammed (Edelweiss Applied Science and Technology, 2024)
In this study, we are used the (3,2) and (4,2) MoS2NTs to deliver OX anticancer drug with and without various impurities and sites in different distance between them. The DFT method is used to compute different electronic properties of the complex structures. We found out that the pristine (3,2) and (4,2) MoS2NTs have semiconductor behavior and the transition of electrons is located at Γ and Z points for (3,2) and (4,2) MoS2NTs, respectively. The complex structure (OX/(3,2)MoS2NTs) has a semimetal behavior with direct transition of electrons at Γ point. There are very interesting results by changing the S atom by P or Ga impurities. So, the (OX/p-doped (3,2) MoS2NTs) structure has a n-type semiconductor behavior when the distance between OX anticancer drug and p-doped (3,2)MoS2NTs is 1.76 Å compared with other distances. By utilizing Ga impurity, the best results are detected at 1.42 Å and the behavior is became p-type behavior and more stable compared to others. For (OX/(4,2)MoS2NTs) has metal behavior. By using P impurity at different distance , the behavior is changed from metal to semi-metal with direct transition at Z point. The behavior of this complex structure is became n-type semiconductor at 1.76 Å. For (OX/Ga-doped (4,2)MoS2NTs) at different distance has a metal behavior , except the 1.82 Å has a n-type semiconductor behavior . The stability of this complex structure became more stable with Ga impurity and the Fermi level is shifted down compared others cases. The stability of all complex structures with Ga impurity is more stable compared with P impurity. In brief, the best substrate of the (3,2) and (4,2) MoS2NTs can be utilized to career OX anticancer drug when we used Ga impurity compared with P impurity.